Tillage of Cover Crops Affects Soil Water, Nitrogen, and Wheat Yield Components. (1st July 2014) - Burgess, Macdonald; Miller, Perry; Jones, Clain; Bekkerman, Anton
Abstract : Annual legume green manure (LGM) cover crops may have potential in dryland wheat ( Triticum aestivum L.) production areas where rotation with whole‐year summer fallow is practiced. No‐till cropland management enhances soil water conservation, possibly enabling cover cropping, but tillage may be necessary to stimulate mineralization of LGM N in time to affect crop yield. A 2‐yr LGM‐wheat crop sequence study was repeated three times in Montana, with mean annual precipitation of 356 mm. Spring‐planted pea ( Pisum sativum L.) and lentil ( Lens culinaris Medik.) The LGM were terminated at first bloom with tillage or herbicide. Post‐termination weed control also was accomplished with either tillage or herbicide in a factorial combination with the termination treatments, resulting in four management regimes. Fallow and non‐N‐fixing cover crop controls were included and subjected to the same management regimes. Spring wheat was grown the following year in subplots with four levels of N fertilizer. Wheat tiller density increased only when LGM was tilled at least once. Tillage also resulted in reduced soil water storage and wheat kernel weight in 1 yr. Effects on grain yield were usually neutral or positive, with pea more frequently having a positive effect than lentil, and interactions with tillage varying each year. Wheat grain protein was increased by pea LGM regardless of tillage, even when LGM did not affect wheat yield, indicating that LGM N supply is accelerated by tillage. Managing LGM in dryland environments involves a tradeoff of soil water for N supply, and tillage affects this balance.